A note on the mapping theorem of essential pseudospectra on a Banach space - Ammar, Aymen; Veeramani, S. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.98The main goal  of the paper is to determine some basic properties of the essential pseudospectrum of a bounded linear operator $A$ defined on a Banach space $X.$ We also  prove two different versions of the essential pseudospectral mapping theorem.